Corrosion survey database (COR SUR)
This database is a collection of the results from numerous literature references reporting the effects of exposing 87 metal and nonmetal materials to over 1500 different exposure media at various temperatures and concentrations resulting in 28,000 pairs of exposed material and medium. The results are presented in searchable tables, and can be browsed by material or exposure medium.
"This database is the online version of NACE COR SUR and COR SUR 2 for Windows and companion volumes, Corrosion data survey - Metals section (6th ed.) and Corrosion data survey - Nonmetals section (5th ed.)."
Chiefly tables.
Keywords: Corrosion and anti-corrosives -- Tables.; elektronické knihy; electronic books